KURIKULUM PONDOK PESANTREN MASA ISLAM DATANG - Tanjung Tanjung (Adisam Publisher, 2024)
Islamic Religious Education (PAI) curriculum material is an integral part of curriculum development in schools and madrasas. The PAI curriculum consists of facts, concepts, principles, laws and skills which aim to develop students' potential holistically, including cognitive, aflective and psychomotor potential. The meaning of